From little things, big things grow: An exploratory analysis of the national cost of peripheral intravenous catheter insertion in Australian adult emergency care. (14th May 2022) - Morgan, Rachel; Callander, Emily; Cullen, Louise; Walker, Katie; Bumpstead, Suzanne; Hawkins, Tracey; Kuhn, Lisa; Egerton‐Warburton, Diana
Abstract: Objective: To estimate the total economic impact of peripheral intravenous catheter (PIVC) or cannula insertion and use in adult Australian EDs, including those cannulas that remain unused for therapeutic purposes. Methods: Searches on Australian government websites were conducted to find rates of insertion, complications and cost of cannula; following this, gaps in national data sets were filled with MEDLINE and PubMed searches to estimate the total cost of cannula use in Australian EDs. Once the data were collected, totals were combined to establish an estimated cost for the listed categories. Results: The estimated cost of cannulation in Australia may be up to A$594 million per year, including the cost of insertion (equipment and staff), cost of complications such as Staphylococcus aureus bacteraemia and phlebitis, and patient‐centred costs (lost patient productivity, infiltration, occlusion and dislodgement). Approximately A$305.9 million is attributed to unused cannulas and approximately 11 790 days of clinician time is spent annually inserting cannula that remains idle. Conclusion: The figures developed in the present study represent an important educational opportunity to encourage thoughtful consideration of all interventions, no matter how small. ED cannula insertion represents a large economic and health cost to Australia's health system, many of which remain unused. There are no national data sets that record complications associated with PIVCs and we highlight the urgent need for improved data. Abstract :